184 Clinical Outcomes of the Prone Transpsoas Lateral Lumbar Interbody Fusion for Degenerative Lumbar Spine Disease: A Multicentre Study. (April 2023) - Soliman, Mohamed A. R.; Diaz-Aguilar, Luis Daniel; Khan, Asham; San Miguel, Jose; Amaral, Rodrigo Augusto; Lee, Bryan S.; Abd-El-Barr, Muhammad M.; Massey, Gene; McMains, Craig; Schwartz, David Gary; Deol, Gurvinder; Nguyen, Andrew D.; et al.
Abstract : INTRODUCTION: The prone transpsoas lateral lumbar interbody fusion (PTP) is a novel technique for degenerative lumbar spine disease. However, there is a paucity of the literature on the clinical outcomes of this procedure, with all the published being of a small sample size. METHODS: A retrospective electronic medical records review was conducted in ten centers for patients who underwent PTP. We collected the intraoperative data (operative time, estimated blood loss [EBL], intraoperative complications [anterior longitudinal ligament (ALL) rupture, cage subsidence, vascular and visceral injuries), postoperative complications, the patient-reported outcome measures (PROMS) such as back pain visual analogue scale (VAS), and hospital stay. RESULTS: A total of 350 patients were included in the study. There was a significant improvement in the mean VAS by 4.4 ± 6.7 (p < 0.001). 2.8% had ALL rupture, 1.2% had cage subsidence, 0.4% had a vascular injury, and none had visceral injuries. The mean operative time was 229.9 ± 144 minutes, the mean EBL was 134.3±210.2 mL, and the mean hospital stay was 2.6 ± 2.2. In regard to postoperative complications, there was 8.9% new sensory symptoms, 6% transient hip flexor weakness, 1.4% wound infection, 1.4% cage subsidence, 0.6% psoas hematoma, 0.3% ureteric injury, 0.3% small bowel obstruction/ischemia, and 1.6% 90-days readmission. CONCLUSIONS: Multicenter consecutive case series show that PTP is well tolerated and has satisfactory clinical outcomes.